2023
DOI: 10.1002/adma.202308774
|View full text |Cite
|
Sign up to set email alerts
|

NIR‐Activatable Heterostructured Nanoadjuvant CoP/NiCoP Executing Lactate Metabolism Interventions for Boosted Photocatalytic Hydrogen Therapy and Photoimmunotherapy

Chunzheng Yang,
Jiashi Zhang,
Mengyu Chang
et al.

Abstract: Near‐infrared (NIR) laser‐induced photoimmunotherapy has aroused great interest due to its intrinsic non‐invasiveness and spatiotemporal precision, while immune evasion evoked by lactic acid (LA) accumulation severely limits its clinical outcomes. Although several metabolic interventions have been devoted to ameliorate immunosuppression, intracellular residual LA still remains a potential energy source for oncocyte proliferation. Herein, we construct an immunomodulatory nanoadjuvant based on a yolk‐shell CoP/N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…H 2 is reported to be an effective antioxidant. 41 TMB and DPPH assays were used to estimate the antioxidant potential of the synthesized hydrogels. The total antioxidant capacity of HAP-Chl was first studied with TMB colorimetric analysis.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…H 2 is reported to be an effective antioxidant. 41 TMB and DPPH assays were used to estimate the antioxidant potential of the synthesized hydrogels. The total antioxidant capacity of HAP-Chl was first studied with TMB colorimetric analysis.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…H 2 is reported to be an effective antioxidant . TMB and DPPH assays were used to estimate the antioxidant potential of the synthesized hydrogels.…”
Section: Resultsmentioning
confidence: 99%
“…Their degradability is crucial to mitigate the potential long-term toxicity of nanomaterials in living organisms. 35 Given the acidic nature of the tumor microenvironment and the presence of excess H 2 O 2 and GSH, we investigated the degradation behavior of BBSP in aqueous solutions with varying conditions, including pH 7.4/H 2 O 2 , 7.4/GSH, 7.4/GSH/H 2 O 2 , and 5.5/GSH/H 2 O 2 . Surprisingly, as depicted in Figure 3a, TEM images revealed that the particle size of BBSP gradually decreased over time at pH 7.4/GSH/ H 2 O 2 .…”
Section: Consumption Of Gshmentioning
confidence: 99%